713 COLLABORATION WITH CARE HOMES TO PROVIDE APPROPRIATE MEDICAL CARE IN THE PANDEMIC. (8th March 2022) - Kelly, S; Griffiths, B; Davies, A; Adenwalla, F
Abstract: Background: The Acute Clinical Team (ACT) in Neath Port Talbot is a well-established hospital at home service that provides treatments in the community. During the COVID 19 outbreaks, the team proactively telephoned the care home managers on a regular basis to enquire about the residents wellbeing and establish if input was required. This proactive approach worked well with some homes. Where crises developed, we were able to provide hands on support to provide appropriate medical care. Methods: A collaborative effort from community teams and volunteers assisted ACT to provide nursing and medical interventions in care homes which accepted our help. Interventions included intravenous (IV) antibiotics, parenteral fluids, IV/oral dexamethasone, low molecular weight heparin, oxygen (up to 10 L face mask), communication with families and palliative care. Results: Data is presented from 7 care homes for which ACT provided input; patients who were unwell requiring additional help were referred to the team. Comparative data from a care home in the same area where ACT was not involved is presented. Data was collected from 01/11/20-10/02/21. Table 1 Care homes with ACT involvement (190 patients) Care home without ACT involvement (85 patients) Patients assessed Patients not assessed No. with COVID-19 infection (%) 96/190 (51%) 94/190 (49%) 27/85 (32%) Acute hospital admission related to COVID-19 (%) 3/96 (3%) 7/94 (9%) 8/27 (30%) Died within 28 days of positive test(%) 37/96 (39%) 20/94 (21%) 15/27 (56%). Conclusion: ACT had a vital role during the outbreak in supporting the local community. The team was able to provide a range of interventions and prevent avoidable admissions. The team received excellent feedback 'We couldn't have survived without the ACT teams input. They were our lifesavers. The whole team were amazing and came to our rescue where everyone else who knew we had COVID bolted to the hills' Manager.